Application of UV absorbance and fluorescence indicators to assess the formation of biodegradable dissolved organic carbon and bromate during ozonation. (15th March 2017) - Li, Wen-Tao; Cao, Meng-Jie; Young, Tessora; Ruffino, Barbara; Dodd, Michael; Li, Ai-Min; Korshin, Gregory
Abstract: This study examined the significance of changes of UV absorbance and fluorescence of dissolved organic matter (DOM) as surrogate indicators for assessing the formation of bromate and biodegradable dissolved organic carbon (BDOC) during the ozonation of surface water and wastewater effluent. Spectroscopic monitoring was carried out using benchtop UV/Vis and fluorescence spectrophotometers and a newly developed miniature LED UV/fluorescence sensor capable of rapidly measuring UVA280 and protein-like and humic-like fluorescence. With the increase of O3 /DOC mass ratio, the plots of BDOC formation were characterized of initial lag, transition slope and final plateau. With the decrease of UV absorbance and fluorescence, BDOC concentrations initially increased slowly and then rose more noticeably. Inflection points in plots of BDOC versus changes of spectroscopic indicators were close to 35–45% loss of UVA254 or UVA280 and 75–85% loss of humic-like fluorescence. According to the data from size exclusion chromatography (SEC) with organic carbon detection and 2D synchronous correlation analyses, DOM fractions assigned to operationally defined large biopolymers (apparent molecular weight, AMW>20 kDa) and medium AMW humic substances (AMW 5.5–20 kDa) were transformed into medium-size building blocks (AMW 3–5.5 kDa) and other smaller AMW species (AMW<3 kDa) associated with BDOC at increasing O3 /DOC ratios. Appreciable bromate formation was observed only after the values of UVA254, UVA280 and humic-like fluorescence in O3 -treated samples were decreased by 45–55%, 50–60% and 86–92% relative to their respective initial levels. No significant differences in plots of bromate concentrations versus decreases of humic-like fluorescence were observed for surface water and wastewater effluent samples. This was in contrast with the plots of bromate concentration versus UVA254 and UVA280 which exhibited sensitivity to varying initial bromide concentrations in the investigated water matrixes. These results suggest that measurements of humic-like fluorescence can provide a useful supplement to UVA indices for characterization of ozonation processes. Graphical abstract: Highlights: BDOC formation was correlated with O3 /DOC ratios and UV/fluorescence indicators. SEC-OCD chromatograms showed changes of MW of DOM caused by ozonation. BrO3 − formation was correlated with O3 /DOC ratios and UV/fluorescence indicators. Changes of fluorescence had a threshold related with the onset of BrO3 − formation. The LED UV/fluorescence sensor was suitable for predicting ozonation performance.